Drinking Water Scarcity in Communities of Surkhet District - Acharya, Chandra Prakash (Karnali Outlook: Knowledge Across Disciplines, 2026)
Access to drinking water is a fundamental necessity for health, well-being, and daily household functioning. This study examined the extent of drinking water shortages and identify the key factors contributing to the scarcity in the area. Employing a quantitative descriptive design with quasi-experimental elements, the study collected primary data from 110 households dependent on tap water supplied by the municipality. Secondary sources, including district profiles, previous research reports, journals, and online publications, were also utilized to provide contextual information. Ethical considerations were strictly maintained throughout the research process. Informed consent was obtained from all respondents prior to data collection, participation was entirely voluntary, and respondents were assured of confidentiality and anonymity. The collected data were used solely for academic purposes. The findings reveal that the majority of households did not experience frequent or severe water shortages, long waiting times, or daily disruptions, and most respondents believed that the existing water system adequately met household needs. However, more than half of the respondents reported reduced water supply during the dry season, indicating seasonal vulnerability. Water scarcity occasionally affected household activities, with causes identified as poor management, population growth, climate change, and infrastructural issues. Households relied on wells, tanker water, or neighbors during shortages and suggested solutions including new water sources, maintenance, rainwater harvesting, and community cooperation. Notably, over half of the respondents expressed willingness to pay higher fees for continuous and safe water supply. The study concludes that while water scarcity in the study area is not severe year-round, targeted improvements in management, infrastructure, and seasonal planning are necessary to ensure sustainable access to drinking water.